Immobile myosin-II plays a scaffolding role during cytokinesis in budding yeast - Wloka, Carsten (The Rockefeller University Press, 2013)
Core components of cytokinesis are conserved from yeast to human, but how these components are assembled into a robust machine that drives cytokinesis remains poorly understood. In this paper, we show by fluorescence recovery after photobleaching analysis that Myo1, the sole myosin-II in budding yeast, was mobile at the division site before anaphase and became immobilized shortly before cytokinesis. This immobility was independent of actin filaments or the motor domain of Myo1 but required a small region in the Myo1 tail that is thought to be involved in higher-order assembly. As expected, proteins involved in actin ring assembly (tropomyosin and formin) and membrane trafficking (myosin-V and exocyst) were dynamic during cytokinesis. Strikingly, proteins involved in septum formation (the chitin synthase Chs2) and/or its coordination with the actomyosin ring (essential light chain, IQGAP, F-BAR, etc.) displayed Myo1-dependent immobility during cytokinesis, suggesting that Myo1 plays a scaffolding role in the assembly of a cytokinesis machine.